2020
DOI: 10.1016/j.dsx.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Is excess weight a risk factor for the development of COVID 19 infection? A preliminary report from India

Abstract: Background and aim This study explored the association between BMI and COVID-19 positive status in a tertiary care hospital from New Delhi. Methods Three hundred and seventy nine adult patients who presented to COVID-19 screening outpatient department of the hospital were interviewed over the phone regarding their body weight and height. The COVID-19 RT-PCR report of the patients was extracted from the hospital information system. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…COVID-19 has swiftly become a global pandemic infecting millions of frontline HCWs with thousands among them succumbing to it [ 5 ]. This alarming rate of infection is attributable to the overburdening of healthcare systems with the rapid surge of patients, shortage of PPE, increased psychosocial stress and lifestyle-related factors, and suboptimal adherence to preventive measures like hand washing and PPE use [ [3] , [4] , [5] , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has swiftly become a global pandemic infecting millions of frontline HCWs with thousands among them succumbing to it [ 5 ]. This alarming rate of infection is attributable to the overburdening of healthcare systems with the rapid surge of patients, shortage of PPE, increased psychosocial stress and lifestyle-related factors, and suboptimal adherence to preventive measures like hand washing and PPE use [ [3] , [4] , [5] , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past pandemics have shown that their impact on lifestyle and mental health can last longer and have greater impact than the pandemic itself (15) . Moreover, it is also seen that weight gain due to positive calorie balance can be a risk factor for development of COVID-19 infections and should be assessed using different tools available in literature (16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous pandemics (SARS, Ebola, H1N1) have revealed that the change in sleep and dietary routine has impacted the lifestyle of individuals was long standing and significant [ 3 , 4 ]. Preventive health measures forced by the government (household confinement, social distancing, and decreased recreational and social activities impacted the lifestyle related behaviours) resulted in adverse metabolic complication such as diabetes, obesity and cardiovascular diseases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%